Complications related to harvest of the proximal end of the fibula: A systematic review. Issue 8 (14th August 2014) - Ben Amotz, Oded; Ramirez, Rey; Husain, Tarik; Lehrman, Craig; Teotia, Sumeet; Sammer, Douglas M.
<x xml:space="preserve">Abstract</x> Background The fibula is a common source of bone graft used in skeletal reconstruction. Although in most cases only the diaphysis of the fibula is used, there are clinical scenarios in which the proximal end of the fibula and fibular head are harvested for use in articular reconstruction. The purpose of this systematic review is to determine the incidence of knee instability and peroneal nerve motor dysfunction associated with removal of the proximal end of the fibula and fibular head. Methods A systematic search was performed using the PubMed, Ovid MEDLINE, and cochrane databases. Studies accepted for review included those that clearly reported donor site morbidity (instability or peroneal nerve motor dysfunction) after proximal fibula resection. All studies in which the proximal fibula was resected for bone graft or for marginal resection of tumor were included. Results Fifteen studies reporting a total of 337 patients were included. The rate of symptomatic knee instability after proximal fibula resection was 3.9%. The incidence of instability that was detectible on physical examination or stress radiographs was higher. Although transient motor dysfunction was not uncommon, the incidence of persistent peroneal nerve motor dysfunction was 2.6%. Conclusion Although asymptomatic laxity is common, the incidence of symptomatic knee instability after resection of the proximal fibula is relatively low. The incidence of persistent peroneal nerve motor dysfunction is also low when the nerve is intentionally protected during surgery. © 2014 Wiley Periodicals, Inc. Microsurgery 34:666–669, 2014.